A Descriptive Study Of Beneficiary Satisfaction Levels With Saudi Red Crescent Services In Major Cities (The Review of Diabetic Studies, 2025)
The study aimed to assess the level of beneficiary satisfaction with the Saudi Red Crescent services in the major cities of the Kingdom by analyzing the quality of field performance and ambulance response. To achieve this objective, the study focused on evaluating several essential dimensions related to the efficiency and effectiveness of prehospital emergency care. These dimensions included the speed of ambulance response, the level of preparedness of ambulance teams, the quality of communication and coordination between emergency dispatch centers and field units, and the overall satisfaction of beneficiaries with the professionalism, empathy, and behavior of paramedics while providing emergency care. The study also explored the adequacy of medical equipment available inside ambulances and its impact on the perceived quality of service. Furthermore, it investigated the extent to which geographical factors—such as the size of major cities, traffic congestion, and population density—affect the response time and service delivery. Demographic factors, including age, education level, and previous experience with emergency services, were analyzed to understand their influence on beneficiary satisfaction levels. Additionally, the research examined public awareness regarding the correct procedures for requesting emergency assistance, the appropriate use of emergency numbers, and the level of community understanding of the Saudi Red Crescent’s role in providing prehospital care. By integrating these elements, the study provides a comprehensive understanding of the strengths and weaknesses of emergency medical services in major urban centers. The findings aim to support decision-makers in enhancing response efficiency, improving beneficiary satisfaction, and developing targeted awareness programs that promote optimal use of emergency services.